HOW MUSTAFA CHOKAI, A PROMINENT HISTORICAL FIGURE OF THE HISTORY OF KAZAKHSTAN’S INDEPENDENCE WAS PRESENTED AS A TRAITOR IN THE SOVIET PERIOD? - Kara, Abdulvahap; Kumganbayev, Zh. (Journal of history, 2017)
In this article, the authors consider the activity of Mustafa Chokay in the way of achieving national independence. Mustafa Chokai was a great Kazakh statesman who accused in the Soviet period of «enemy of the people», «counter-revolutionary element», «bourgeois nationalist», «fascist ally» , «traitor» and «creator of the Turkestan Legion» etc. The reason for this that the main idea of political activity of Chokay was to establish an independent national goverment instead of the Soviet regime in Turkestan. The name of Chokai mentioned in the history books of the Soviet Period as a traitor who betrayed their homeland. The authors of the article analyze the Soviet propaganda against the Chokai. Concerning this considered KGB officer, Serik Shakibayev’s book entitled «The collapse of Great Turkistan». This essay was presented as a documentary novel in which revealed Chokai as a traitor who sold home for the sake of the Nazi ranks and titles.